Evolusi darwinisme vs penciptaan manusia dalam perspektif islam - Udma, Aufini Afifatul (Maliki Interdisciplinary Journal, 2024)
Human evolution is the evolutionary process in primate history that led to the separation of Homo Sapiens as a separate species from the Hominidae (including the great apes). This process involved the gradual evolution of traits such as bipedal locomotion and language in humans, as well as interbreeding with other humans, suggesting that human evolution was not linear but interrelated. This article discusses the differences between Darwin's and Harun Yahya's theories of human creation. The problem is that these two his theories of human origin contradict each other. Therefore, this article aims to explore the differences between these two theories so that their approaches can be analyzed.